The Role of ASEANAPOL in Tackling Human Trafficking Issue in Indonesia in 2021-2023 - Najib, Gesang; Juned, Mansur (Jurnal Ilmu Kepolisian, 2025)
This research discusses the role of ASEANAPOL in assisting Indonesia in tackling human trafficking issue by using cases that took place throughout 2021-2023 through series of its agendas and activities. This research uses Clive Archer's role theory which states that international organizations have roles in arenas, instruments, and actors. The method used in conducting this research is descriptive qualitative method with the data obtained from literature review, official documents analysis, interviews with the relevant actors, and secondary sources that relevant to the research topic. The findings of this research reveal that ASEANAPOL has a significant role in assisting Indonesia in tackling human trafficking issue by utilizing its instrument, arena of expertise, and relevant stakeholders to facilitate meetings and exchange information. The maximization of functions can be conducted if the decision-makers of each member state could create a strong legal framework in order to enable some flexibility for ASEANAPOL to deal with human trafficking cases that arise. This research concludes that it is fundamental to acknowledge ASEANAPOL’s role in human trafficking eradication in Indonesia. Therefore, this research recommends the Indonesian government, ASEAN member states, and ASENAPOL to further develop a system with a firm commitment and legal framework to ensure human trafficking eradication is well-executed.